The parametric excitation of ion Bernstein modes at the ICR plasma heating in the U-3M torsatron - Olshansky, V.V.; Stepanov, K.N.; Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Skibenko, A.I.; Volkov, E.D. (Вопросы атомной науки и техники, 2009)
The results of theoretical and experimental investigations of oscillatory and wave processes at the stellarator plasma edge are presented. Experimental results were interpreted using the kinetic theory of the electron-ion parametrical instability. It is shown that the interaction between plasma and the alternating electric field under conditions carried out in given experiment makes possible a parametric excitation of the ion cyclotron oscillations.